Pengaruh Bank Syariah terhadap Pertumbuhan Ekonomi di Indonesia - Salahuddin El Ayyubi; Lukytawati Anggraeni; Almira Dyah Mahiswari (Department of Islamic Economics, IPB University, 2017)
Financial sector have important role to develop economic growth in the country. Aim of this study are to analyze the causality between Islamic Banking towards economic growth in Indonesia, the response of economic growth in Indonesia during the shock of Islamic banking and the contribution from Islamic banking towards economic growth in Indonesia. The data used in this study is monthly report during 2010 – 2016. Analysis of the data used Vector Error Corection Model (VECM). The results are significant effect and bidirectional causality appears between financing and Gross Dosmetic Product (GDP). Impulse Resonse Function (IRF) analysis shows that response of economic growth is different between the shock on Islamic financing and Third Party Funds (DPK). Based on Forecast Error Variance Decomposition (FEVD), financing have greatest contribution towards the effect of economic growth but DPK have less contribution. In conclusion Islamic banking should have more efficient during the allocation of DPK to financing.